Calendar Aging of Lithium-Ion Batteries: I. Impact of the Graphite Anode on Capacity Fade. Issue 9 (1st January 2016) - Keil, Peter; Schuster, Simon F.; Wilhelm, Jörn; Travi, Julian; Hauser, Andreas; Karl, Ralph C.; Jossen, Andreas
Abstract : In this study, the calendar aging of lithium-ion batteries is investigated at different temperatures for 16 states of charge (SoCs) from 0 to 100%. Three types of 18650 lithium-ion cells, containing different cathode materials, have been examined. Our study demonstrates that calendar aging does not increase steadily with the SoC. Instead, plateau regions, covering SoC intervals of more than 20%–30% of the cell capacity, are observed wherein the capacity fade is similar. Differential voltage analyses confirm that the capacity fade is mainly caused by a shift in the electrode balancing. Furthermore, our study reveals the high impact of the graphite electrode on calendar aging. Lower anode potentials, which aggravate electrolyte reduction and thus promote solid electrolyte interphase growth, have been identified as the main driver of capacity fade during storage. In the high SoC regime where the graphite anode is lithiated more than 50%, the low anode potential accelerates the loss of cyclable lithium, which in turn distorts the electrode balancing. Aging mechanisms induced by high cell potential, such as electrolyte oxidation or transition-metal dissolution, seem to play only a minor role. To maximize battery life, high storage SoCs corresponding to low anode potential should be avoided.